P605 Eight-year efficacy and safety of azathioprine treatment in the maintenance of steroid-free remission in inflammatory bowel disease patients. (15th January 2020) - Cassieri, C; Pica, R; Avallone, E V; Brandimarte, G; Zippi, M; Crispino, P; De Nitto, D; Lecca, P G; Vernia, P; Pica, R; Corazziari, E S
Abstract: Background: Azathioprine (AZA) and thiopurine are widely used for induction and maintenance of remission in steroid-dependent patients with inflammatory bowel disease (IBD). The aim of this study has been to investigate its efficacy and safety in maintaining steroid-free remission in steroid-dependent IBD patients eight years after the institution of treatment. Methods: Data from consecutive IBD outpatients referred in our Institution, between 1985–2017, were reviewed and all patients treated with AZA were included in this retrospective study. AZA was administered at the recommended dose of 2–2.5 mg/kg. Results: Out of 2992 consecutive IBD outpatients visited in the index period, AZA was prescribed to 446 patients, 245 (54.9%) were affected by Crohn's disease (CD) and 201 (45.1%) by ulcerative colitis (UC). One hundred and ninety-six patients with a follow-up < 96 months were excluded from the study. Two hundred and fifty patients were evaluated, 140 (56%) with CD and 110 (44%) with UC. One hundred and thirty-eight (55.2%) were male and 112 (44.8%) female (average age of 35.48 ± 14.26 SD years, range 14–74 years). Eight year after the institution of treatment, 123 (49.2%) patients still were in steroid-free remission (82 CD vs. 41 UC, 58.6% and 37.3%, respectively, p = 0.0009), 71 (28.4%) had a relapse requiring retreatment with steroids (29 CD vs. 42 UC, 20.7% and 38.2%, respectively, p = 0.0030), 56 (22.4%) discontinued the treatment due to side effects (29 CD vs. 27 UC, 20.7% and 24.5%, respectively). The loss of response from first to eighth year of follow-up was low, about 21%. Conclusion: Eight years after the onset of treatment about 50% of patients did not require further steroid courses. After the first-year loss of response was low in seven subsequent years. In the present series, the maintenance of steroid-free remission was significantly higher in CD than in UC patients. The occurrence of side effects leading to the withdrawal of AZA treatment has been low.